PERLINDUNGAN HUKUM TERHADAP EKSPRESI BUDAYA TRADISIONAL DALAM PERSPEKTIF UNDANG UNDANG HAK CIPTA - Djaja, Hendra (Jurnal Cakrawala Hukum, 2016)
According to the statistics year 2010 in Indonesia there are more than a thousand nations across Nusantara so that Indonesia is very rich in diversity of the traditional cultural expressions.The traditional cultural expressions are â€œintangible culture creationâ€ an ancestral estate that must be maintained, maintained, developed and protected from exploitation and unilateral claim a foreign country or misappropriation. The creator of the work of cultural expression generally not recognized, so that an obligation to protect the traditional cultural expressions especially being on the state as copyright holders and to indigenous as caretaker the origin of the birth of creation culture it. jika ownership of intellectual property in regime trips is individual so that in protection the traditional cultural expressions ownership of their rights are communal namely to be shared indigenous caretaker creation traditional culture concerned. As the holder of the power of the traditional cultural expressions, the government is given the right of the management or a right economic exploitation (economic rights) an expression of the traditional culture of rights moralnya while (moral rights), remain on the community. The law enforcement abuse of the traditional cultural expressions existing during this is less exhilarating. Several factors thought to cause the ineffectiveness of law enforcement abuse by foreign parties claiming unilaterally cultural expression the traditional. Copyright Act Number 28 Year 2014 expected more effective in legal protection the traditional cultural expressions.